2017
DOI: 10.1016/j.metabol.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of essential amino acid supplementation in stimulating whole body net protein anabolism is comparable between COPD patients and healthy older adults

Abstract: Background The development of effective nutritional strategies in support of muscle growth for patients with chronic obstructive pulmonary disease (COPD) remains challenging. Dietary essential amino acids (EAAs) are the main driver of postprandial net protein anabolism. In agreement, EAA supplements in healthy older adults are more effective than supplements with the composition of complete proteins. In patients with COPD it is still unknown whether complete protein supplements can be substituted with only EAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…Valine is a metabolite that also promotes muscle growth and overall muscle health. Jonker et al reported that an essential amino acid supplement that includes valine, could be used as a treatment for COPD to prevent muscle wasting [39].…”
Section: Discussionmentioning
confidence: 99%
“…Valine is a metabolite that also promotes muscle growth and overall muscle health. Jonker et al reported that an essential amino acid supplement that includes valine, could be used as a treatment for COPD to prevent muscle wasting [39].…”
Section: Discussionmentioning
confidence: 99%
“…These determine the AA composition, leucine concentration, protein digestibility and subsequent availability of absorbed AA for protein synthesis (12,(88)(89)(90)(91)(92)(93) . Jonker et al recently found that a high-leucine EAA mixture was superior to a similar mixture with the AA composition of complete proteins, in improving wholebody net protein gain (94) , and suggests possible benefits and effectiveness of EAA over complete protein (92) .…”
Section: Most Effective Supplementmentioning
confidence: 99%
“…In COPD patients, free essential amino acid supplements stimulate whole-body protein anabolism more than free amino acid supplements. 41 Nutritional supplementation also enriched with leucine, vitamin D, and omega-3 fatty acids increased inspiratory muscle strength and maintained physical activity. 42 Thus, in addition to pulmonary rehabilitation, combined supplements with free EAA, vitamin D, and polyunsaturated fatty acids may be helpful for the prevention and treatment of skeletal muscle wasting and an improvement in body composition in waiting list patients.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, free essential amino acid supplements stimulate whole-body protein anabolism more than free amino acid supplements 41. To increase skeletal muscle mass but not body fat mass, enough energy and sufficient supply of amino acids are needed.…”
mentioning
confidence: 99%